GDF11 inhibits abnormal adipogenesis of condylar chondrocytes in temporomandibular joint osteoarthritis - Helin Wang; Yuqian Shi; Feng He; Tao Ye; Shibin Yu; Hui Miao; Qian Liu; Mian Zhang (Bone & Joint Research, 2022)
Aims: Abnormal lipid metabolism is involved in the development of osteoarthritis (OA). Growth differentiation factor 11 (GDF11) is crucial in inhibiting the differentiation of bone marrow mesenchymal stem cells into adipocytes. However, whether GDF11 participates in the abnormal adipogenesis of chondrocytes in OA cartilage is still unclear. Methods: Six-week-old female mice were subjected to unilateral anterior crossbite (UAC) to induce OA in the temporomandibular joint (TMJ). Histochemical staining, immunohistochemical staining (IHC), and quantitative real-time polymerase chain reaction (qRT-PCR) were performed. Primary condylar chondrocytes of rats were stimulated with fluid flow shear stress (FFSS) and collected for oil red staining, immunofluorescence staining, qRT-PCR, and immunoprecipitation analysis. Results: Abnormal adipogenesis, characterized by increased expression of CCAAT/enhancer-binding protein α (CEBPα), fatty acid binding protein 4 (FABP4), Perilipin1, Adiponectin (AdipoQ), and peroxisome proliferator-activated receptor γ (PPARγ), was enhanced in the degenerative cartilage of TMJ OA in UAC mice, accompanied by decreased expression of GDF11. After FFSS stimulation, there were fat droplets in the cytoplasm of cultured cells with increased expression of PPARγ, CEBPα, FABP4, Perilipin1, and AdipoQ and decreased expression of GDF11. Exogenous GDF11 inhibited increased lipid droplets and expression of AdipoQ, CEBPα, and FABP4 induced by FFSS stimulation. GDF11 did not affect the change in PPARγ expression under FFSS, but promoted its post-translational modification by small ubiquitin-related modifier (SUMOylation). Local injection of GDF11 alleviated TMJ OA-related cartilage degeneration and abnormal adipogenesis in UAC mice. Conclusion: Abnormal adipogenesis of chondrocytes and decreased GDF11 expression were observed in degenerative cartilage of TMJ OA. GDF11 supplementation effectively inhibits the adipogenesis of chondrocytes and thus alleviates TMJ condylar cartilage degeneration. GDF11 may inhibit the abnormal adipogenesis of chondrocytes by affecting the SUMOylation of PPARγ. Cite this article: Bone Joint Res 2022;11(7):453–464.